Uji Toksistas Subkronik 28 Hari Ekstrak Metanolik kombinasi Daun Benalu Teh dan Benalu Mangga terhadap fungsi Hepar Pada Tikus (Rattus norvegicus) Betina - Hatif Khusnin Nida'; Nour Athiroh Abdoes Sjakoer; Nurul Jadid Mubarakati (Jurnal Ilmiah Biosaintropis (Bioscience -Tropic), 2022)
ABSTRACT Flavonoids and quercetin are metabolite compounds contained in parasite plants. The role of the compounds is as an antioxidant that can protect cell damage from free radicals,for example liver. The presence of antioxidant can neutralize and protect the liver from free radicals. Liver is an organ that is vulnerable to damage caused by drugs or toxic chemicals because the liver is the center of metabolism in the body. Can be known with indicators of increasing level of SGOT, SGPT total bilirubin and histopathologic liver. The purpose of this study to determine the effect of the combination of extracts of tea parasite and mango parasite (EMBTBM) on levels of liver function in female rats (Rattus norvegicus) for 28 days. Data were analyzed using ANOVA version Jamovi 1.0.1.0.. The number of test animals is 20 female rats were divided into four groups, group 1 as a control, group 2,3,4 as a treatment. The treatment groups was given EMBTBM with different doses of 250 mg/kgBW, 500 mg/kgBW and 1000 mg/kgBW. Based on the research results show that a significant value difference between the group was p> 0,05. Therefore EMBTBM given to female rats for 28 days with a dose of 250 mg/BW, 500 mg/kgBW and 1000 mg/kgBW in the treatment group all dose were not significantly different compared with controls. So that the level of liver function in female rats was safe (not toxic) and has no effect on liver histopathology of female wistar rats. Keyword: Subchronic, Extract and liver function